The use of ileocolic segment for esophageal replacement in children - Harshjeet Singh Bal; Sudipta Sen (Wolters Kluwer Medknow Publications, 2016)
Aims: To evaluate and describe the procedure and outcome of ileocolic replacement of esophagus. Materials and Methods: We review 7 children with esophageal injuries, who underwent esophageal replacement using ileocolic segment in Christian Medical College, Vellore, India between 2006 and 2014. Results: The ileocolic segment was used in 7 children with scarred or inadequate esophagus. There were 4 girls and 3 boys, who underwent esophageal replacement using isoperistaltic ileocolic segment in this period. Age at presentation varied from 1 month to 14 years with an average of 4.6 years. The indications for ileocolic replacements were corrosive strictures in 5, failed esophageal atresia repair in one and gastric volvulus related esophageal stricture in another. The average follow-up duration was 37 months. One child with corrosive stricture lost to follow-up and died 2 years later in another center. Other 6 children were free of dysphagia till the last follow-up. Conclusions: Although the ileocolic segment is not commonly used for esophageal substitution, it can be useful in special situations where the substitution needs to reach the high cervical esophagus and also where the stomach is scarred and not suitable for gastric pull-up.